Reliable outcome parameters in patients with lumbar radiculopathy attributed to disc herniation: an observational study - Bianchi, Giannina; Zweifel, Christian; Hohenauer, Erich; Santos, Joseph Alvin Ramos; Clijsen, Ron (Frontiers in Musculoskeletal Disorders, 2025)
IntroductionEvidence regarding the diagnostic accuracy of physical assessments and patient-reported outcome measures in lumbar disc herniation with radiculopathy remains inconclusive. This study aimed to evaluate whether selected patient-reported outcome measures and physical assessments accurately reflect treatment progress, regardless of whether the treatment was conservative only or combined with surgery.MethodsMobility, isometric strength, pain, numbness, paresthesia, Oswestry Disability Index, International Physical Activity Questionnaire, straight-leg raising test, and the Short Form-36 Health Survey physical and mental components were recorded at baseline, after six weeks, and at six months.ResultsAt six weeks (n = 19), significant improvements were observed in the straight-leg raising test (mean difference: 10.53, 95% CI: 1.25–19.81, p = 0.02), the Short Form-36 Health Survey physical component score (9.06, 95% CI: 4.23–13.90, p < 0.001), and the mental component score (10.29, 95% CI: 4.81–15.76, p < 0.001), pain sensation (−2.46, 95% CI: −3.99–−0.93, p < 0.001), paresthesia (−2.36, 95% CI: −3.73–−0.99, p < 0.001), numbness (−1.35, 95% CI: −2.56–−0.14, p = 0.023), and in the Oswestry Disability Index score (−20.42, 95% CI: −28.04–−12.80, p < 0.001). At six months (n = 15), significant benefits were noted in anterior flexion (−8.19, 95% CI: −13.42–−2.96, p = 0.001), back extension (9.35, 95% CI: 4.52–14.18, p < 0.001), and muscle strength in the affected leg (tibialis anterior muscle: 44.27, 95% CI: 4.72–83.81, p = 0.024; extensor hallucis longus muscle: 16.58, 95% CI: 2.60–30.56, p = 0.02). No significant changes occurred in lateral flexion left or right, strength in the unaffected leg, or the International Physical Activity Questionnaire.ConclusionThe exploratory findings of this study indicate that subjective outcomes improve earlier than objective measures. These findings emphasize the value of combining subjective and objective methods to monitor treatment outcomes and assess progress effectively. Larger studies with more participants, frequent evaluations, and longer follow-up are needed to clarify recovery patterns, determine the most sensitive outcome measures, and define minimal clinically important differences for patients with lumbar disc herniation with radiculopathy.